An Artificial Skyrmion Platform with Robust Tunability in Synthetic Antiferromagnetic Multilayers. (22nd October 2019) - Li, Yong; Feng, Qiyuan; Li, Sihua; Huang, Ke; Ma, Mangyuan; Gan, Weiliang; Zhou, Haibiao; Jin, Xiangjun; Renshaw Wang, Xiao; Lu, Yalin; Lew, Wen Siang; Lu, Qingyou; et al.
Abstract: Magnetic skyrmions are topologically nontrivial spin structures, and their existence in ferromagnetically coupled multilayers has been widely reported with a disordered arrangement. Here, a nucleation scenario of ordered skyrmions in nanostructured synthetic antiferromagnetic (SAF) multilayers is proposed and experimentally demonstrated using direct magnetization imaging, indirect magnetometer and magnetoresistance measurement, and micromagnetic simulation. Instead of relying on Dzyaloshinskii–Moriya interaction, the antiferromagnetic interlayer exchange coupling in the SAF multilayers fulfills the role of nucleation and stabilization of skyrmions. The robustness of the proposed skyrmion nucleation scenario is examined against temperature from 4.5 to 300 K and device size from 400 to 1200 nm. Interestingly, these synthetic skyrmions still behave well with a size less than 100 nm. The higher stability than generic magnetic domains can be attributed to topological protection. The results thus provide an artificial skyrmion platform to meet the functional needs of high density and designable arrangement in magnonic and spintronic applications. Abstract : Artificial skyrmions in synthetic antiferromagnetic multilayers are robust against temperature and device size as guaranteed by the antiferromagnetic interlayer exchange coupling. These synthetic skyrmions exhibit a high tunability and are still well behaved with a size less than 100 nm. Moreover, the designable arrangement according to the functional demands can be realized with nanolithography.